Clinicopathologic Features and Response to Therapy of NRG1 Fusion–Driven Lung Cancers: The eNRGy1 Global Multicenter Registry. Issue 25 (1st September 2021) - Drilon, Alexander; Duruisseaux, Michael; Han, Ji-Youn; Ito, Masaoki; Falcon, Christina; Yang, Soo-Ryum; Murciano-Goroff, Yonina R.; Chen, Haiquan; Okada, Morihito; Molina, Miguel Angel; Wislez, Marie; Brun, Philippe; et al.
Abstract : PURPOSE: Although NRG1 fusions are oncogenic drivers across multiple tumor types including lung cancers, these are difficult to study because of their rarity. The global eNRGy1 registry was thus established to characterize NRG1 fusion–positive lung cancers in the largest and most diverse series to date. METHODS: From June 2018 to February 2020, a consortium of 22 centers from nine countries in Europe, Asia, and the United States contributed data from patients with pathologically confirmed NRG1 fusion–positive lung cancers. Profiling included DNA-based and/or RNA-based next-generation sequencing and fluorescence in situ hybridization. Anonymized clinical, pathologic, molecular, and response (RECIST v1.1) data were centrally curated and analyzed. RESULTS: Although the typified never smoking (57%), mucinous adenocarcinoma (57%), and nonmetastatic (71%) phenotype predominated in 110 patients with NRG1 fusion–positive lung cancer, further diversity, including in smoking history (43%) and histology (43% nonmucinous and 6% nonadenocarcinoma), was elucidated. RNA-based testing identified most fusions (74%). Molecularly, six (of 18) novel 5′ partners, 20 unique epidermal growth factor domain–inclusive chimeric events, and heterogeneous 5′/3′ breakpoints were found. Platinum-doublet and taxane-based (post–platinum-doublet) chemotherapy achieved low objective response rates (ORRs 13% and 14%, respectively) and modest progression-free survival medians (PFS 5.8 and 4.0 months, respectively). Consistent with a low programmed death ligand-1 expressing (28%) and low tumor mutational burden (median: 0.9 mutations/megabase) immunophenotype, the activity of chemoimmunotherapy and single-agent immunotherapy was poor (ORR 0%/PFS 3.3 months and ORR 20%/PFS 3.6 months, respectively). Afatinib achieved an ORR of 25%, not contingent on fusion type, and a 2.8-month median PFS. CONCLUSION: NRG1 fusion–positive lung cancers were molecularly, pathologically, and clinically more heterogeneous than previously recognized. The activity of cytotoxic, immune, and targeted therapies was disappointing. Further research examining NRG1 -rearranged tumor biology is needed to develop new therapeutic strategies.